Radiotherapy for Oligometastases and Oligo-Recurrence of Bone in Prostate Cancer. (9th September 2012) - Tabata, Ken-ichi; Niibe, Yuzuru; Satoh, Takefumi; Tsumura, Hideyasu; Ikeda, Masaomi; Minamida, Satoru; Fujita, Tetsuo; Ishii, Daisuke; Iwamura, Masatsugu; Hayakawa, Kazushige; Baba, Shiro
Abstract : Purpose . To retrospectively evaluate the clinical significance of radiotherapy for oligometastases of bone in prostate cancer (PCa). Methods and Materials . Between 2003 and 2008, 35 PCa patients with oligometastases of bone were treated with radiotherapy. Results . The median radiotherapy dose was 40 Gy. The 3-year overall survival rates for all patients, for patients that received a radiotherapy dose of ≥40 Gy (n = 21 ) and for those that received <40 Gy (n = 14 ), were 77.2%, 90.5%, and 50.0%, respectively. Fourteen out of 16 patients (87.5%) who had pain were improved 1 month after radiotherapy. The median duration of pain relief was 12 months. Pathological fracture and spinal cord compression (SCC) were not seen at the treated sites but developed at nonirradiated sites in three patients (8.6%) and in one patient (2.8%), respectively. Although the high-dose group (≥40 Gy) achieved better survival than the low-dose group (<40 Gy), it was not independent prognostic factor in multivariable analysis. Conclusions . Radiotherapy of bone oligometastases in PCa was effective for long-term pain relief. Pathological fracture and SCC were not seen at the treated sites. A larger clinical trial is warranted to study the actual benefit following radiotherapy for oligometastases of bone in PCa.